Cognitive Hyperconnected Digital Transformation : Internet of Things Intelligence Evolution. - Vermesan, Ovidiu. (River Publishers, 2017)
Cognitive Hyperconnected Digital Transformation provides an overview of the current Internet of Things (IoT) landscape, ranging from research, innovation and development priorities to enabling technologies in a global context.